Peran Guru IPS dalam Menginternalisasikan Nilai-Nilai Multikulturalisme pada Siswa SMP - Faisol Hakim; Babul Bahrudin; Fika Anjana (Universitas Muhammadiyah Mataram, 2025)
Abstract: Indonesia is a multicultural country with diverse ethnicities, religions, cultures, and languages that serve as both a source of richness and a potential source of conflict if not properly managed. Education plays an important role in internalizing the values of multiculturalism. This study aims to analyze the role of social studies (IPS) teachers in internalizing multicultural values and their implementation in students’ social interactions at SMP Negeri 1 Kraksaan. The focus of the research lies on three aspects of the teacher’s role exemplary behavior, teaching and learning activities, and habituation and four dimensions of multicultural values: tolerance, democracy, equality, and pluralism. The study employs a qualitative approach with a case study design, chosen to explore the meanings, experiences, and actions of teachers and students in a contextual manner. Data were collected through interviews, observations, and documentation. The informants consisted of the principal, social studies teachers, and students selected through purposive sampling. Data analysis followed the Miles and Huberman model, which includes data collection, data condensation, data display, and conclusion drawing. Data validity was tested through source, method, and theoretical triangulation. Albert Bandura’s social learning theory served as the analytical foundation. The results show that social studies teachers play an active role in instilling the values of tolerance, democracy, equality, and pluralism through exemplary conduct, the application of inclusive learning strategies, and the habituation of mutual respect. These findings confirm Albert Bandura’s social learning theory, emphasizing that observation and modeling are essential mechanisms in shaping students’ multicultural behavior. Students learn by imitating teachers who demonstrate fairness, openness, and respect for differences. This study contributes to the development of multicultural-based social studies learning practices by highlighting the teacher’s role as a social agent and model of multicultural behavior who fosters an inclusive learning climate, strengthens tolerant attitudes, and cultivates awareness of diversity in schools.Abstrak: Indonesia merupakan negara multikultural dengan beragam suku, agama, budaya, dan bahasa yang menjadi kekayaan sekaligus potensi konflik jika tidak dikelola dengan baik. Pendidikan berperan penting dalam menginternalisasikan nilai multikulturalisme. Penelitian ini bertujuan menganalisis peran guru IPS dalam menginternalisasikan nilai-nilai multikulturalisme serta implementasinya dalam interaksi sosial siswa di SMP Negeri 1 Kraksaan. Fokus penelitian ini pada tiga aspek peran guru: keteladanan, KBM, pembiasaan dan empat dimensi nilai multikulturalisme: toleransi, demokrasi, kesetaraan, dan pluralisme. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Pendekatan ini dipilih untuk menggali makna, pengalaman, serta tindakan guru dan siswa secara kontekstual. Data dikumpulkan melalui wawancara, observasi, dokumentasi. Informan terdiri dari kepala sekolah, guru IPS, dan siswa yang dipilih secara purposive. Analisi data menngunakan Miles dan Huberman, yang mencakup pengumpulan data, kondensasi data, penyajian data, dan penarikan kesimpulan. Keabsahan data diuji melalui triangulasi sumber, metode, dan teori. Teori belajar social Albert Bandura sebagai landasan analisis. Hasil penelitian menunjukkan bahwa guru IPS berperan aktif dalam menanamkan nilai toleransi, demokrasi, kesetaraan, dan pluralisme melalui aspek keteladanan, penerapan strategi pembelajaran inklusif, dan pembiasaan sikap saling menghargai. Temuan ini mengonfirmasi teori belajar sosial Albert Bandura, bahwa proses observasi dan modeling merupakan mekanisme penting dalam pembentukan perilaku multikultural siswa. Siswa belajar meniru perilaku guru yang menunjukkan keadilan, keterbukaan, dan penghargaan terhadap perbedaan. Penelitian ini berkontribusi terhadap pengembangan praktik pembelajaran IPS berbasis multikulturalisme, dengan menegaskan bahwa guru berperan sebagai agen sosial dan model perilaku multikultural yang mampu membentuk iklim belajar inklusif, memperkuat sikap toleran, dan menumbuhkan kesadaran kebinekaan di sekolah.